1993
DOI: 10.1111/j.1440-1681.1993.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

11β‐HYDROXYSTEROID DEHYDROGENASE ACTIVITY IN MESENTERIC ARTERIES OF SPONTANEOUSLY HYPERTENSIVE RATS

Abstract: 1. 11 beta-Hydroxysteroid dehydrogenase (11-HSD) activity in mesenteric arteries of spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats was determined and expressed as the percentage conversion of [3H]-corticosterone to [3H]-11-dehydrocorticosterone. 2. 11-HSD activity was significantly decreased in mesenteric arteries of both 4 and 9 week old SHR (8.4 +/- 0.8%, 5.0 +/- 1.5%, respectively) compared with WKY rats (12.4 +/- 0.6%, 15.8 +/- 0.7%, respectively; P < 0.05). 3. Total RNA from rat vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Decreased 11␤-HSD activity has been demonstrated in some patients with essential hypertension [1][2][3] and in rats with genetic hypertension. 4,5 Biochemical studies have revealed the existence of 2 isoforms of 11␤-HSD: NAD ϩ dependent and NADP ϩ dependent. 11␤-HSDII (the NAD ϩ -dependent isoform) is found in distal portions of the nephron, where it has been shown to colocalize with mineralocorticoid receptors.…”
mentioning
confidence: 99%
“…Decreased 11␤-HSD activity has been demonstrated in some patients with essential hypertension [1][2][3] and in rats with genetic hypertension. 4,5 Biochemical studies have revealed the existence of 2 isoforms of 11␤-HSD: NAD ϩ dependent and NADP ϩ dependent. 11␤-HSDII (the NAD ϩ -dependent isoform) is found in distal portions of the nephron, where it has been shown to colocalize with mineralocorticoid receptors.…”
mentioning
confidence: 99%
“…The authors (19) demonstrated the expression of 1119-HSD in the mesenteric artery by immunocytochemical staining methods, in situ hybridization, and by Northern blot analysis. Therefore, it is likely that 1119-HSD activity is diminished at the site of resistance vessels per se, as we demonstrated for the mesenteric artery of spontaneously hypertensive rats (21). If this is true in primary hypertension, the vasoconstrictor response to cortisol would be potentiated, even in minor stressful conditions, through the enhanced binding of cortisol to the mineralocorticoid receptor.…”
Section: Altered Steroid Metabolismmentioning
confidence: 80%
“…[11][12][13][14][15][16] Although the kidney plays a major role in sodium homeostasis and has often been implicated in the pathogenesis of hypertension, no differences of renal 11␤HSD were observed between Milan hypertensive rats and their normotensive counterparts, 11 whereas 11␤HSD activity was found to be increased in mesenteric arteries and decreased in the hearts of SHR. 13,14 Recently, the decrease of renal 11␤HSD was reported in hypertensive DS in comparison with the normotensive DR rats.…”
mentioning
confidence: 80%
“…However, it has recently been reported that the mesenteric enzyme activity is significantly decreased in both SHR and DS-HS rats compared with their normotensive counterparts. 12,14 It means that there are not uniform changes in enzyme activity in different parts of the cardiovascular systems of normotensive and hypertensive rats or that the differences result from differences in techniques used (homogenate v perfusion of isolated arteries). The reaction direction of 11␤HSD (11␤HSD-1) depends on the cell context/local environment and therefore the direction of the reaction in homogenate does not always reflect the activity of the intact tissue.…”
Section: Fig 3 11␤hsd Activity In Ds and Dr Rats Fed A High-salt DImentioning
confidence: 99%